A review of the removal of microplastics in global wastewater treatment plants: Characteristics and mechanisms. (January 2021) - Liu, Weiyi; Zhang, Jinlan; Liu, Hang; Guo, Xiaonan; Zhang, Xiyue; Yao, Xiaolong; Cao, Zhiguo; Zhang, Tingting
Graphical abstract: Highlights: Quantitative analysis is used to evaluate the removal of microplastics in global WWTPs. The filter-based technologies perform better microplastics removal efficiency. Mechanisms of critical treatment technologies in microplastics removal are summarized. An average of 7.2 billion day −1 microplastics entered the river from WWTPs. Specific microplastics shall be highlighted besides the common microplastics. Abstract: Wastewater treatment plants (WWTPs) are considered to be the main sources of microplastic contaminants in the aquatic environment, and an in-depth understanding of the behavior of microplastics among the critical treatment technologies in WWTPs is urgently needed. In this paper, the characteristics and removal of microplastics in 38 WWTPs in 11 countries worldwide were reviewed. The abundance of microplastics in the influent, effluent, and sludge was compared. Then, based on existing data, the removal efficiency of microplastics in critical treatment technologies were compared by quantitative analysis. Particularly, detailed mechanisms of critical treatment technologies including primary settling treatment with flocculation, bioreactor system, advanced oxidation and membrane filtration were discussed. Thereafter, the abundance load and ecological hazard of the microplastics discharged from WWTPs into the aquatic and soil environments were summarized. The abundance of microplastics in the influent ranged from 0.28 particles L −1 to 3.14 × 10 4 particles L −1, while that in the effluent ranged from 0.01 particles L −1 to 2.97 × 10 2 particles L −1 . The microplastic abundance in the sludge within the range of 4.40 × 10 3 –2.40 × 10 5 particles kg −1 . In addition, there are still 5.00 × 10 5 –1.39 × 10 10 microplastic particles discharged into the aquatic environment each day Moreover, among the critical treatment technologies, the quantitative analysis revealed that filter-based treatment technologies exhibited the best microplastics removal efficiency. Fibers and microplastics with large particle sizes (0.5–5 mm) were easily separated by primary settling. Polyethene and small-particle size microplastics (<0.5 mm) were easily trapped by bacteria in the activated sludge of bioreactor system. The negative impact of microplastics from wastewater treatment plant was worthy of attention. Moreover, unknown transformation products of microplastics and their corresponding toxicity need in-depth research.